Sustainability Analysis and Strategy to Increase Company Value - Fazora, Vienna Afwani; Helmi, Syarif M.; Heniwati, Elok (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This article discusses the phenomenon of Livestreamers and Vtubers that are becoming increasingly popular in the digital entertainment industry. Livestreamers and Vtubers use virtual avatar technology to interact with live audiences through live broadcasts. The concept of avatars in the virtual world allows users to create unique and interesting digital representations. In addition, the article also discusses the internal conflicts that occurred between Vtubers and their agencies, as well as the social and reputational impact of the company after significant changes. Using a conflict management approach, this research identifies the sources of conflict and seeks constructive solutions. Case studies were conducted to analyze the change in a specific context and understand its impact. In addition, the article also discusses the theory of corporate sustainability in supporting the growth and sustainability of the Vtuber agency. Thus, this article provides an in-depth insight into the current trends in digital entertainment and their implications for the entertainment industry as a whole.